Harnessing the dual role of polysaccharides in treating gastrointestinal diseases: As therapeutics and polymers for drug delivery. (1st December 2022) - Corrie, Leander; Gulati, Monica; Awasthi, Ankit; Vishwas, Sukriti; Kaur, Jaskiran; Khursheed, Rubiya; Porwal, Omji; Alam, Aftab; Parveen, Shaik Rahana; Singh, Hardeep; Chellappan, Dinesh Kumar; Gupta, Gaurav; et al.
Abstract: Polysaccharides (PS) represent a broad class of polymer-based compounds that have been extensively researched as therapeutics and excipients for drug delivery. As pharmaceutical carriers, PS have mostly found their use as adsorbents, suspending agents, as well as cross-linking agents for various formulations such as liposomes, nanoparticles, nanoemulsions, nano lipid carriers, microspheres etc. This is due to inherent properties of PS such as porosity, steric stability and swellability, insolubility in pH. There have been emerging reports on the use of PS as therapeutic agent due to its anti-inflammatory and anti-oxidative properties for various diseases. In particular, for Crohn's disease, ulcerative colitis and inflammatory bowel disease. However, determining the dosage, treatment duration and effective technology transfer of these therapeutic moieties have not occurred. This is due to the fact that PS are still at a nascent stage of development to a full proof therapy for a particular disease. Recently, a combination of polysaccharide which act as a prebiotic and a probiotic have been used as a combination to treat various intestinal and colorectal (CRC) related diseases. This has proven to be beneficial, has shown good in vivo correlation and is well reported. The present review entails a detailed description on the role of PS used as a therapeutic agent and as a formulation pertaining to gastrointestinal diseases. Highlights: Polysaccharides (PS) have been widely used in various drug delivery technologies. PS act via the MAPK and PI3/AKT signaling pathways to treat gastrointestinal diseases. Probiotics and PS together are used as therapeutic agent as well as pharmaceutical carrier. PS are used as crosslinking agents, stabilizing agents, solidifying and coating agents.